Timor Etnográfico: antropologia e arquivo colonial - Roque, Ricardo (2017)
This article examines the world of colonial ethnographies in Timor-Leste, designated Portuguese Timor, during the Portuguese colonial period in the twentiethcentury. It argues for the significance of a history of anthropology that focuses on the plurality of ethnographic practices and knowledge forms in colonial situation. The article discusses current research on colonial ethnographies in the Portuguese Empire, with reference to the articles and contributions contained in the special issue Ethnographic Timor: Anthropology and the Colonial Archive.